A compositional approach to concurrent object-oriented programming - Pandey, R.; Browne, J.C. (Proceedings of 1994 IEEE International Conference on Computer Languages (ICCL'94), 1994)
Presents a model of concurrent object-oriented programming in which specification of computational behavior is separated from specification of interaction behavior of methods. This compositional approach to concurrent programming avoids some of the conceptual difficulties that have plagued the integration of concurrency and object-oriented models of programs. The compositional approach to concurrent object-oriented programming leads to declarative and incremental specification of interaction behavior and, thus, to object/method definitions that can be readily adapted to different parallel execution environments. The approach supports inheritance of both method and synchronization specifications. Compositional programming avoids the so-called "inheritance anomaly".< >